Strategic Management as the Foundation of Visionary Leadership - Sa’idy; Agus Faisal Asyha; Sunarto (Tadrib: Jurnal Pendidikan Agama Islam, 2024)
This study aims to analyze the role of strategic management in improving educational quality through visionary leadership at MAN 1 Bandar Lampung and MAN 1 Kota Metro. The research employs a qualitative method with a case study approach. The findings show that at MAN 1 Bandar Lampung, strategic management and visionary leadership successfully enhanced educational quality by developing technology-based flagship programs and ongoing teacher training. In contrast, at MAN 1 Kota Metro, the lack of optimal strategic management implementation and limited visionary leadership hindered the institution's progress, particularly in evaluation and resource management. The study concludes that the synergy between strategic management and visionary leadership is key to achieving educational success. Recommendations include strengthening the evaluation of strategic programs at MAN 1 Bandar Lampung and developing a more structured strategic plan at MAN 1 Kota Metro, focusing on leadership development and continuous teacher training.